Syntenin Regulated by miR-216b Promotes Cancer Progression in Pancreatic Cancer - Zu, Fuqiang; Chen, Hui; Liu, Qingfeng; Zang, Hui; Li, Zeyu; Tan, Xiaodong (Frontiers in Oncology, 2022)
Outcomes for patients with pancreatic cancer (PC) are poor; therefore, there is an urgent need to identify novel therapeutic targets involved in the progression of PC. We previously identified 161 differentially expressed proteins (DEPs) in PC. Syntenin (SDCBP) was identified as a survival-related protein through integrated, survival, and Cox analyses. High expression of SDCBP was associated with a poor prognosis in PC tissue and promoted the proliferation, migration and invasion of PC cells, and induced epithelial-mesenchymal transition (EMT) via the PI3K/AKT pathway. Additionally, we elucidated the regulatory mechanism underlying these roles of SDCBP at the post-transcriptional level. microRNAs (miRNAs) of SDCBP were predicted using bioinformatics. Low levels of miR-216b expression were confirmed in PC tissues and were negatively correlated with SDCBP expression. miR-216b was found to directly regulate SDCBP expression through luciferase reporter assays. Furthermore, agomiR-216b restrained PC proliferation, migration, invasion, and EMT via the PI3K/AKT pathway, whereas antagomiR-216b facilitated this process. Notably, the knockout of SDCBP counteracted the effect of antagomiR-216b in PC, which suggested that miR-216b and SDCBP represent molecular targets underlying PC progression and EMT. Finally, the results were validated in in vivo studies. These findings indicated that low expression of miR-216b and the oncogene SDCBP contribute to PC migration, invasion, and EMT, and have potential as future therapeutic targets for patients with PC.